1997
DOI: 10.1002/mds.870120629
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of blink rate patterns in normal subjects

Abstract: The present study measured the normal blink rate (BR) variations in relation to behavioral tasks in 150 healthy volunteers (70 males and 80 females; aged 35.9 +/- 17.9 years, range 5-87 years). The subjects were videotaped in a standard setting while performing three different tasks: resting quietly, reading a short passage, talking freely. The mean BR was computed during each task; the data were compared by means of analysis of variance and Student's t tests. Mean BR at rest was 17 blinks/min, during conversa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
317
5
16

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 421 publications
(362 citation statements)
references
References 12 publications
(4 reference statements)
24
317
5
16
Order By: Relevance
“…Typical blink frequencies at rest range from about 12 to 20 blinks/minute (15,41), lowest at a discrete observation (42). In a study of 150 healthy subjects, the most common order of decreasing blink frequency was found to be conversation > rest > reading (43). Blink frequency during reading also depends on the position of the gaze, being lowest during a low gaze (44).…”
Section: Factors Influencing Blinking and The Formation Of Tear Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical blink frequencies at rest range from about 12 to 20 blinks/minute (15,41), lowest at a discrete observation (42). In a study of 150 healthy subjects, the most common order of decreasing blink frequency was found to be conversation > rest > reading (43). Blink frequency during reading also depends on the position of the gaze, being lowest during a low gaze (44).…”
Section: Factors Influencing Blinking and The Formation Of Tear Filmmentioning
confidence: 99%
“…However, blink frequency is also influenced by psychological and mental states of mind. For example, mental stress, cognitive awareness and demands, and the tasks performed can play a role (15,43,44). In addition, increased attention generally decreases blink frequency, while anxiety or high arousal increases it (60), in addition to conversation (43).…”
Section: Factors Influencing Blinking and The Formation Of Tear Filmmentioning
confidence: 99%
“…Some previous works have studied blink variations in regard to modality (visual versus acoustic) [13] or location (central versus peripheral) [6] of presenting stimuli. Another research has measured the blink rate in resting, reading and talking conditions [1]. A few studies have examined blink features in two cognitive load levels and found them related with mental load level [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…On average, people blink 15-17 times a minute (Bentivoglio etal.1997;Karsonetal.1990)withtheratechangingaccordingto differentmentalstatessuchasreading,talking,daydreaming,and resting (Bentivoglio et al 1997;Doughty 2001). When asked, subjects can inhibit their EB to some extent for a limited amount of time (Mazzone et al, 2010;Moraitis and Ghosh 2014;SchmeichelandZell2007).TheabilitytoinhibitEBcanbemoderatelypredictedbyaself-controlreport,i.e.,peoplewhoreported themselveshighonself-controlinhibitedEBbetterthatthosewho reported themselves low on the trait scale (Schmeichel and Zell 2007).…”
Section: Introductionmentioning
confidence: 99%